Analisis Pengaruh Digitalisasi Masjid terhadap Spiritualitas Mahasiswa Muslim - Hartono, Alya Khairina; Rahmadhani, Asri Suci; Saefi, Masropah Humaya; Aprilliawan, Muhamad Nursalam; Aulia, Naura Rahma; Permadi, Salma Fadhillah; Parhan, Muhamad (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2026)
This research aims to analyze the role and measure the influence of Mosque Digitalization on the Spirituality of Muslim Students in Indonesia. Mosque digitalization, utilizing social media, especially Instagram, has transformed the religious interaction of the younger generation. The study employed a quantitative approach with a descriptive correlational design using a survey method. Data were collected from 100 Muslim student respondents across various universities using a Likert-scale questionnaire. The results indicate that mosque digitalization has a positive and significant influence on the spirituality of Muslim students. Collectively, the majority of respondents (86%) reported benefits, especially in fostering discipline in worship (80% aided by digital tools) and expanding access to dakwah and information (84% rated as effective). Nevertheless, the impact of digitalization on intrinsic motivation for worship and physical participation in religious studies remains moderate, evident from the high percentage of indifferent respondents. The conclusion of this study is that Mosque Digitalization plays a positive and significant role in supporting and strengthening Muslim Student Spirituality.